PENGARUH INSENTIF PAJAK KENDARAAN BERMOTOR SELAMA PANDEMI COVID 19, SOSIALISASI DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI BANTEN - Taufik Hidayat (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2022)
The purpose of this study was to determine the effect of Motor Vehicle Tax Incentives during the Covid 19 Pandemic, Tax Socialization, Tax Sanctions on Motor Vehicle Taxpayer Compliance. This research is a quantitative research with an associative approach. The sample used in this study was 42 respondents who were in the South Tangerang area. The sampling method used is purposive sampling. Data collection in this study was carried out using primary data, namely field research by distributing questionnaires to the intended research subjects. The results of the study show that Motor Vehicle Tax Incentives During the Covid 19 Pandemic and Tax Socialization have no effect on Motor Vehicle Taxpayer Compliance. Meanwhile, Tax Sanctions affect the Compliance of Motorized Vehicle Taxpayers.